Sufi Islamic Discourse in Africa: From the Greatest Jihad to the Establishment of the African Caliphate - Ḥasan, Ḥamdī ʿAbd-ar-Raḥmān (Religions, 2020)
In the nineteenth century, African Muslim societies were marked by the emergence of a reformist Sufi Islamic discourse aimed at changing and moving away from traditional Islamic practices. Although this discourse was influenced, to some extent, by external sources of inspiration, it was linked to the local African context. This study demonstrates that the reformist discourse of major Sufi figures such as Sheikh Amadu Bamba in Senegal and Sheikh Usman Dan Fodio in Nigeria reflects a number of common features of Islamic reform in Africa, yet their reform programs were shaped by the conditions of the local context. This research contribution aims to understand the actual role that the discourse of Sufi spirituality played—and still does—in the religious, economic, and political life of Muslim societies in Africa. This study has shown that despite the prevailing belief that Sufi discourse does not tend to politicize as it tries to maintain a safe distance away from matters of politics and governance in order to achieve its message of moral and spiritual purity, it may turn into violent radicalism as embodied by the jihadist Sufi experience in West Africa.